On some aspects of diabatic heating and vertical velocity - Singh, U.S.; Rathor, H.S. (MAUSAM, 1975)
Negelecting the effects of friction from the complete vorticity and thermodynamic equation in the derived equation, they have three different terms of forcing. From these relations we have computed vertical velocity due to diabatic heating.